Consideration in Randomized Placebo-Controlled Trial on Neck Pain to Avoid the Placebo Effect in Analgesic Action - Sun, Yue-Li; Yao, Min; Zhu, Yue-Feng; Yin, Meng-Chen; Liu, Jin-Tao; Chen, Xin; Huang, Jin; Dai, Yu-Xiang; Wang, Wen-Hao; Ma, Zeng-Bin; Wang, Yong-Jun; Cui, Xue-Jun (Frontiers in Pharmacology, 2022)
Background: In neck pain treatment, many therapies are focused on etiology, while it is well-known that placebo analgesia is also present in these therapies. The specific efficacy for etiology may be underestimated by ignoring their actual placebo effect. In this study, a logistic regression analysis is used to explore the risk factors causing different placebo responses in patients with neck pain among two RCTs. The probability of the placebo effect is predicted based on these risk factors. Methods: Trial A and Trial B were similarly designed, randomized, double-/single-blind, placebo-controlled trials in patients treating neck pain with Qishe pill or Shi-style manipulation. Both studies set a placebo pill twice a day or traction for every other day as control. For further analyses on the placebo effect in neck pain management, logistic regression was used to assess subgroup-placebo interactions. The odds ratio assessed a significant influence on the placebo effect. Results: In this pooled analysis, the total number of patients recruited for these two studies was 284, of which 162 patients received placebo treatment (placebo drug or traction for every other day). No statistically significant differences are found at baseline between the participants with placebo effect and non-placebo effect in the gender, age, and disease duration except in VAS and NDI at the initial time. There are numerically more patients with placebo effect in the shorter disease duration subgroup (< 4 months [76%]), higher initial VAS subgroup (>60 mm [90%]), and worse initial NDI subgroup (>24 [72%]) compared with the gender and age subgroup. An ROC curve is established to assess the model-data fit, which shows an area under the curve of 0.755 and a 95% confidence interval of 0.677–0.830. Participants who show placebo effect after 2 weeks have significantly lower VAS scores after 4 weeks, while there is no significant difference in NDI improvement between the two groups after 4 weeks. Conclusion: Neck pain patients with shorter disease duration are more likely to overscore their pain severity, because of their less experience in pain perception, tolerance, and analgesia expectation.